2022
DOI: 10.1007/s12088-022-01024-x
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Biotechnological Potential of Marine Actinomycetes from India

Abstract: Actinomycetes are potential antibiotic producers that have been isolated from various terrestrial ecosystems and are exploited for their bioactive compounds. On the contrary, the marine environments were less explored and the research on marine actinomycetes had gained momentum only for the past three decades. Marine actinomycetes are one of the most significant producers of diverse groups of secondary metabolites and provide a huge scope for pharmaceutical and other industries. These organisms are proved to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 48 publications
(44 reference statements)
0
15
0
2
Order By: Relevance
“…In post-harvest fruit management, antagonists are subjected to changes in pH, temperature, and humidity because in these conditions the efficiency of biocontrol agents can be affected [ 99 ]. Actinomycetes from marine, saline, hypersaline, and wetland environments are subjected to extreme environmental conditions that allow them to adapt to the changes in temperature, pH, and humidity that occur post-harvest [ 19 , 100 ]. However, in most of the studies of actinomycetes and biocontrol of phytopathogenic fungi in post-harvest fruit, the isolates provided are from terrestrial environments ( Figure 4 ).…”
Section: Antifungal Activity Of Actinomycetes Isolated In Different E...mentioning
confidence: 99%
“…In post-harvest fruit management, antagonists are subjected to changes in pH, temperature, and humidity because in these conditions the efficiency of biocontrol agents can be affected [ 99 ]. Actinomycetes from marine, saline, hypersaline, and wetland environments are subjected to extreme environmental conditions that allow them to adapt to the changes in temperature, pH, and humidity that occur post-harvest [ 19 , 100 ]. However, in most of the studies of actinomycetes and biocontrol of phytopathogenic fungi in post-harvest fruit, the isolates provided are from terrestrial environments ( Figure 4 ).…”
Section: Antifungal Activity Of Actinomycetes Isolated In Different E...mentioning
confidence: 99%
“…BCy which was isolated from Cymodocearotundata seagrass using two different media [18], Sarkar and Suthindhiran (2022) also suggested the diversity of marine actinobacteria from different marine ecosystems and found 30 types of actinobacteria from various types of seaweed such as Cymodaceae sp., Enhalus sp., Halophila sp., Halodule sp., Syringodium sp., and Thalassia sp. [19]. In addition, the diversity of heterotroph bacteria in seagrass ecosystems was also shown by Boontanom and Chantarasiri (2020), who found a diversity of 9 isolates of epiphytic bacteria isolated from seaweed (Halodule uninervis) [20].…”
Section: Morphological Characteristics Of Cellulolytic Bacterial Isol...mentioning
confidence: 78%
“…Because nearly 80% of our collection was able to use CMC as only carbon source, we evaluated cellulose degradation in CCM1 agar medium in terms of enzymatic index (EI) to select the best possible cellulolytic candidate. Calculating EI is used to evaluate enzyme-producing prospects within the same genus ( Teather & Wood, 1982 ) and was previously used for this purpose in other studies ( Barzkar & Sohail, 2020 ; Fatokun, Nwodo & Okoh, 2016 ; Lewin et al., 2022 ; Sarkar & Suthindhiran, 2022 ). In this study, 12 out of 196 strains showed high EI values (≥ 3.0) and were considered as highly cellulolytic, so they were selected for further quantitative enzymatic assays ( Fig.…”
Section: Discussionmentioning
confidence: 99%